Fat & fabulous: Bifunctional lipids in the spotlight - Haberkant, Per; Holthuis, Joost C.M. (Biochimica et biophysica acta, 2014)
Understanding biological processes at the mechanistic level requires a systematic charting of the physical and functional links between all cellular components. While protein–protein and protein–nucleic acid networks have been subject to many global surveys, other critical cellular components such as membrane lipids have rarely been studied in large-scale interaction screens. Here, we review the development of photoactivatable and clickable lipid analogues–so-called bifunctional lipids–as novel chemical tools that enable a global profiling of lipid–protein interactions in biological membranes. Recent studies indicate that bifunctional lipids hold great promise in systematic efforts to dissect the elaborate crosstalk between proteins and lipids in live cells and organisms. This article is part of a Special Issue entitled Tools to study lipid functions. •We report on a novel technique using photoactivatable and clickable–so-called bifunctional–lipids•Bifunctional lipids allow for the proteomic profiling of protein–lipid interactions in living cells•The technology provides means for the imaging of protein–lipid complexes